2D Numerical Simulation and Sensitive Analysis of H-Darrieus Wind Turbine - Saryazdi, Seyed Mohammad E.; Boroushaki, Mehrdad (International Journal of Renewable Energy Development, 2018)
Recently, a lot of attention has been devoted to the use of Darrieus wind turbines in urban areas. The aerodynamics of a Darrieus turbine are very complex due to dynamic stall and changing forces on the turbine triggered by changing horizontal angles. In this study, the aerodynamics of H-rotor vertical axis wind turbine (VAWT) has been studied using computational fluid dynamics via two different turbulence models. Shear stress transport (SST) k-Ï‰ turbulence model was used to simulate a 2D unsteady model of the H-Darrieus turbine. In order to complete this simulation, sensitivity analysis of the effective turbine parameters such as solidity factor, airfoil shape, wind velocity and shaft diameter were done. To simulate the flow through the turbine, a 2D simplified computational domain has been generated. Then fine mesh for each case consisting of different turbulence models and dimensions has been generated. Each mesh in this simulation dependent on effective parameters consisted of domain size, mesh quality, time step and total revolution. The sliding mesh method was applied to evaluate the unsteady interaction between the stationary and rotating components. Previous works just simulated turbine, while in our study sensitivity analysis of effective parameters was done. The simulation results closely match the experimental data, providing an efficient and reliable foundation to study wind turbine aerodynamics. This also demonstrates computing the best value of the effective parameter. The sensitivity analysis revealed best value of the effective parameter that could be used in the process of designing turbine. This work provides the first step in developing an accurate 3D aerodynamic modeling of Darrieus wind turbines.Article History: Received :August 19th 2017; Received: December 15th 2017; Accepted: Januari 14th 2018; Available onlineHow to Cite This Article: Saryazdi, S. M. E. and Boroushaki, M. (2018) 2D Numerical Simulation and Sensitive Analysis of H-Darrieus Wind Turbine. Int. Journal of Renewable Energy Development,7(1),23-34https://doi.org/10.14710/ijred.7.1.23-24